Stereographic projections path integral for inertia ellipsoids: Applications to Arn–HF clusters - Russo, M. F.; Curotto, E. (The Journal of chemical physics, 2004)
The DeWitt formula for inertia ellipsoids mapped by stereographic projection coordinates is developed. We discover that by remapping the quaternion parameter space with stereographic projections, considerable simplification of the differential geometry for the inertia ellipsoid with spherical symmetry takes place. The metric tensor is diagonal and contains only one independent element in that case. We find no difficulties testing and implementing the DeWitt formula for the inertia ellipsoids of asymmetric tops mapped by stereographic projections. The path integral algorithm for the treatment of Rm⊗S2 manifolds based on a mixture of Cartesian and stereographic projection coordinates is tested for small Arn–HF clusters in the n=2 to n=5 range. In particular, we determine the quantum effects of the red shift and the isomerization patterns at finite temperatures. Our findings are consistent with previously reported computations and experimental data for small Arn–HF clusters.